2020
DOI: 10.24270/tuuom.2020.29.8
|View full text |Cite
|
Sign up to set email alerts
|

Vitsmunaleg áskorun í stærðfræðikennslu á unglingastigi

Abstract: Markmið þessarar myndbandsrannsóknar var að meta vitsmunalega áskorun í stærðfræðikennslu á unglingastigi. Alls voru 34 kennslustundir í stærðfræði í 8. bekk í 10 skólum teknar upp og greindar ásamt 144 viðfangsefnum sem lögð voru fyrir. Greining gagna leiddi í ljós að meirihluti viðfangsefna fól í sér að beita tilteknum reikniaðferðum við úrlausn þeirra. Jafnframt virtist kennurum reynast vandasamt að viðhalda kröfum um rökhugsun í kennslustundum. Þegar nemendur unnu hver fyrir sig eftir áætlun var algengt að… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…In the study, the potential for cognitively activating instruction was analysed using mathematical tasks as the unit of analysis, which is a common method (see e.g. Neubrand et al, 2013;Sigurjónsson & Gísladóttir, 2020;Tekkumru-Kisa et al, 2020). This method of analysis may include either tasks as exercises from textbooks and other learning materials, or tasks from tests and examinations.…”
Section: Cognitive Activationmentioning
confidence: 99%
See 2 more Smart Citations
“…In the study, the potential for cognitively activating instruction was analysed using mathematical tasks as the unit of analysis, which is a common method (see e.g. Neubrand et al, 2013;Sigurjónsson & Gísladóttir, 2020;Tekkumru-Kisa et al, 2020). This method of analysis may include either tasks as exercises from textbooks and other learning materials, or tasks from tests and examinations.…”
Section: Cognitive Activationmentioning
confidence: 99%
“…Subsequent studies have reported the same common instructional pattern, with student collaboration and teacher-facilitated mathematical discussions existent but uncommon (Gunnarsdóttir & Pálsdóttir, 2015;Sigurgeirsson et al, 2014). In most mathematics lessons, the selected tasks are low-level, or the teachers' implementation of tasks results in low intellectual challenge (Sigurjónsson & Gísladóttir, 2020).…”
Section: Mathematics Teaching In Icelandmentioning
confidence: 99%
See 1 more Smart Citation